Industrial waste fly ash cenosphere composites based broad band microwave absorber. (1st February 2018) - Bora, Pritom J.; Porwal, Mayuri; Vinoy, K.J.; Kishore,; Ramamurthy, Praveen C.; Madras, Giridhar
Abstract: The utilization of industrial waste fly ash cenosphere (FAC) for microwave absorption is explored in this study. FAC, the industrial waste, was pre-treated with conventional acid-base wash. As soft magnetic metal oxides are viewed with interest for microwave applications owing to their possessing many advantageous properties, in this work, NiO and CoOX was coated over FAC by chemical precipitation and thermal reduction method for studying the microwave absorption property. The polyvinylbutyral (PVB)-FAC, PVB-CoOx -FAC and PVB-NiO-FAC composites were prepared by solution processing and dielectric property study was carried out in X-band (8.2–12.4 GHz) and Ku-band (12.4–18 GHz) microwave frequencies. The minimum reflection loss (RL) was observed for PVB-NiO-FAC composite in a large band width as compared to PVB-CoOx -FAC and PVB-FAC composites. In the X-band, the lowest RL value of PVB-NiO-FAC composite was observed to be ∼−32 dB (∼12.3 GHz) and it decreased to ∼−49.7 dB in the Ku-band (15.8 GHz). Additionally, the thickness dependent RL was also studied for all the composites. The enhancement of EM attenuation constant and loss factor (LF) was found to be intrinsically high for PVB-NiO-FAC composite along with dielectric dissipation as compared to other composites (i.e., PVB-FAC and PVB-CoOx -FAC) pointing to its excellent microwave absorption property. Therefore, the prepared composites are suitable for microwave absorption based applications such as radar, robotic engineering, military applications, electromagnetic gasket, aircraft and unmanned vehicles. Graphical abstract: